Optimal global carbon management with ocean sequestration - Wilfried Rickels; Thomas S. Lontzek (Kiel Institute for the World Economy (IfW), 2008)
We investigate the socially optimal anthropogenic intervention into the global carbon cycle. The limiting factor for this intervention is the accumulation of carbon in the atmosphere, which causes global warming. We apply a simplified two-box model to incorporate aspects of the global carbon cycle in a more appropriate way than a simple proportional decay assumption does. Anthropogenic intervention into the global carbon cycle enters the model as the amount of CO2 emitted into the atmosphere and the amount of CO2 injected into the deep ocean for purposes of sequestration. We derive a critical cost level for sequestration above which sequestration is just a temporary option or below which it is the long-run option allowing extended use of fossil fuels. The second option involves higher atmospheric stabilization levels, whereby the efficiency of sequestration depends on the time preference and the inertia of the carbon cycle.
Keywords: Q30; Q54; Q30; 330; Global Carbon Cycle; Sequestration; CO2 Emissions; Climate Change; Klimaschutz; Kohlenstoffsenke; Kohlendioxid; Meer; Kosten-Nutzen-Analyse; Theorie